Il santo premostratense Ermanno Giuseppe di Colonia: lettere postulatorie e documenti inediti sulla sua "strana canonizzazione" - Maleczek, Werner ("Libellus quasi speculum". Studi offerti a Bernard Ardura, 2022)
Keywords: 👤 hermann of cologne

‘Ante omnia, fratres carissimi, diligatur Deus, deinde proximus’: Herman/Judah’s Opusculum de conversione sua Re-examined - Hames, Harvey J. (Conﬂict and Religious Conversation in Latin Christendom: Studies in Honour of Ora Limor, 2014)
Keywords: 👤 hermann of cologne

The Conversion of Herman the Jew: Autobiography, History, and Fiction in the Twelfth Century - Schmitt, Jean-Claude (University of Pennsylvania Press, 2012)
Keywords: 👤 hermann of cologne

Me peperit ecclesia mater. Einige Bemerkungen zur Selbstdarstellung Hermanns von Köln in seinem Opusculum de conversione sua - Gäbe, Sabine (Analecta Praemonstratensia, 2000)
Looking at the Opusculum from a literary studies perspective (form, stylizing, stereotyped attitudes, intention, reader’s point of view) one arrives at the following results: The descriptio historiae consists of a continuous description of the internal, spiritual, and intellectual struggle of the autobiographical ego. Individual experiences of his life are only reported in so far as they are important for the progression of conversion. „Historical Persons“ mentioned in the text do not have their own personality: Jews are stylized as adversaries of the conversion (according to the stereotyped attitudes stemming from the theological tradition). Christians, however, are made into role models. The identity of the autobiographical writer is the identity of an ordained Christian priest. His former Jewish identity is portrayed as „non-identity“. The intention of the work is not to be, as it was assumed in the past, a defence against the reproach that the conversion took place for opportunistic reasons. Nor is it an attempt to respond with anti-Semitic comments to latent hostile feelings against the former Jew. On the contrary, the intention is to show Christian readers an example of how to part Jews from their „hardening“ and win them for Christianity by gentleness and charity. The work attempts, as the second Crusade quickly approaches (among other things) to support efforts that defend Jews from encroachments.
Keywords: 👤 hermann of cologne